EVALUASI GEOMETRIK - KINERJA DAN PERKERASAN LENTUR JALAN RAYA BALURAN KM 248 – KM 250 KABUPATEN SITUBONDO - Rofieq, Muh. Nizar Junaidi Ainur; Hamduwibawa, Rofi Budi; Manggala, Adhitya Surya (Universitas Muhammadiyah Jember, 2019)
Â The importance of improving land transportation infrastructure which can support the smooth and equitable development, therefore roads are an important facility for humans to reach an area that they want to reach. The highway is a track that aims to pass traffic from one place to another. The north coast highway (Pantura) is a highway that falls within the criteria of a road which is heavily passed by heavy vehicles because, Baluran highway is a connecting road between Situbondo district and Banyuwangi district. Baluran road conditions are winding and there are slopes (vertical). With a width of road = 7 meters, this highway is passed by heavy vehicles. This solid volume of vehicles results in overloading of the road resulting in frequent damage to the road body. In addition, sharp curves (horizontal curves) and slope and grade slopes (vertical curves) coupled with conditions around the shoulders of trees which also provide poor visibility. Considering the above conditions (geometric and flexible pavement) on the Baluran highway, re-evaluation or analysis of the length of the curvature (horizontal and vertical curves) is required, in addition to the frequent damage to the road body, an evaluation of the thickness of the flexible pavement is needed.